The Arabidopsis minE mutation causes new plastid and FtsZ1 localization phenotypes in the leaf epidermis - Fujiwara, Makoto T.; Kojo, Kei H.; Kazama, Yusuke; Sasaki, Shun; Abe, Tomoko; Itoh, Ryuuichi D. (Frontiers in Plant Science, 2015)
Plastids in the leaf epidermal cells of plants are regarded as immature chloroplasts that, like mesophyll chloroplasts, undergo binary fission. While mesophyll chloroplasts have generally been used to study plastid division, recent studies have suggested the presence of tissue- or plastid type-dependent regulation of plastid division. Here, we report the detailed morphology of plastids and their stromules, and the intraplastidic localization of the chloroplast division-related protein AtFtsZ1-1, in the leaf epidermis of an Arabidopsis mutant that harbors a mutation in the chloroplast division site determinant gene AtMinE1. In atminE1, the size and shape of epidermal plastids varied widely, which contrasts with the plastid phenotype observed in atminE1 mesophyll cells. In particular, atminE1 epidermal plastids occasionally displayed grape-like morphology, a novel phenotype induced by a plastid division mutation. Observation of an atminE1 transgenic line harboring an AtMinE1 promoter::AtMinE1-yellow fluorescent protein fusion gene confirmed the expression and plastidic localization of AtMinE1 in the leaf epidermis. Further examination revealed that constriction of plastids and stromules mediated by the FtsZ1 ring contributed to the plastid pleomorphism in the atminE1 epidermis. These results illustrate that a single plastid division mutation can have dramatic consequences for epidermal plastid morphology, thereby implying that plastid division and morphogenesis are differentially regulated in epidermal and mesophyll plastids.